The asymmetric effect of income and price changes on the consumption expenditures : evidence from G7 countries using nonlinear bounds testing approach - Wang, Xi (2024)
Previous studies mainly focused on linear models to examine the relationship between price changes, income changes, and consumption expenditures. However, the recent literature supports the nonlinear relationship between economic and fnancial varia bles. This study contributes to the existing literature using a novel approach called the nonlinear ARDL model. This model helps to examine the efect of positive and nega tive shocks in income and price changes on consumption expenditures. Based on the nonlinear ARDL model, the fndings indicate that an increase in income signifcantly and positively afects household consumption expenditures in the short and long run. In contrast, a decrease in income does not signifcantly afect consumption. Likewise, price changes are unimportant in explaining the changes in consumption expendi tures in the selected countries. Therefore, our fndings support the use of this novel technique to examine the nonlinear nature of the relationship among the given vari ables. These fndings provide important policy implications concerning the positive and negative shocks of the exogenous variables on the dependent variables implying that devising the same policies during increasing and decreasing income and prices may lead to unfavorable consequences that hamper economic growth.